Parents’ rearing styles and adolescents’ math achievement: the multiple mediating effect of self-control and math anxiety - Wang, Yanjiao; Han, Lei; Tao, Yang; Ma, Yanyan (Frontiers in Psychology, 2024)
Introduction This cross-sectional study examined the mechanisms underlying adolescent math achievement by investigating the relationship between parents’ rearing styles (including different dimensions of rearing style) and adolescent self-control, math anxiety, and math achievement based on the ecological systems theory. Method A total of 584 junior high school students (M age = 12.52) completed the Parenting Style Questionnaire, Self-control Scale, and Math Anxiety Rating Scale and provided their math test scores. Results The rearing styles of both fathers and mothers directly predicted adolescents’ math achievement. Maternal rearing style indirectly predicted adolescents’ math achievement through their self-control and math anxiety; however, the indirect effect of paternal rearing style on adolescents’ math achievement was not significant. After distinguishing the three dimensions of rearing styles, we found that paternal emotional warmth can increase adolescents’ self-control, while maternal emotional warmth can reduce adolescents’ self-control. Further, paternal overprotectiveness can directly and positively predict adolescents’ math achievement, while maternal rejection and overprotectiveness can positively predict adolescents’ math achievement. None of the three dimensions of rearing styles can predict math achievement through adolescents’ self-control; however, they can predict math achievement indirectly through adolescents’ math anxiety and the chain-mediation of adolescents’ self-control and math anxiety. Discussion Our results suggest both commonalities and differences in how paternal and maternal rearing styles, along with their three dimensions (emotional warmth, rejection, overprotection), predict adolescent math achievement. These findings highlight the importance of paternal and maternal rearing styles on adolescents’ math achievement and underscore the need to examine them separately to better understand their impact.